The developments in the central business district of Istanbul in the 1990s - Dilek Ozdemir (European Regional Science Association (ERSA), 2002)
Since the 1980s, the economic and political conjuncture of the world has changed to a great extent leading to profound transformations in cities and metropolitan areas. Economic restructuring, globalization process, and re-organization of central-local government relations are the basic factors behind these transformations In a similar vein, after the mid-1980s and throughout the 1990s, the development of Istanbul metropolitan area have been characterized by a variety of factors ranging from the implementation of the neoliberal policies at the national level to the changes in the metropolitan government at the local level. Although the roots of this transformation can be traced back to the late-1970s, the most important changes have taken place in the last two decades. After 1980, Turkey adopted neoliberal policies in order to increase its economic articulation to the international relations. As a result of these measures, starting from the mid-1980s, foreign direct investment inflows into Turkey have increased to a great extent. Moreover, parallel to the worldwide trend of rising importance of producer services, the share of service sector investments has increased in total amount of foreign direct investment inflows into Turkey. During this period, Istanbul metropolitan area and especially its Central Business District (CBD) was affected to a great extent by the implementation of private sector-led projects realized by both foreign and Turkish firms operating in various activities such as retailing, tourism, real-estate, finance and other producer services. The author argues that the neoliberal policies of the central government after the 1980s, the increase in foreign direct investments in service sector, the investment shift from industry to commercial and residential real-estate development and financial activities have brought about significant transformations in Istanbul metropolitan area. In this work, in the light of the above-mentioned factors, the development of the Istanbul metropolitan area (especially its CBD development), in the late 1980s and throughout the1990s, will be analyzed.
Keywords: 330